Effect of Strengthening Exercises and Muscle Stimulator in Hirayama Disease Patients Having Muscle Atrophy and Weakness : A Case Report - Sapkota, Nabin; Shrestha, Rakesh; Bhurtel, Bidur; Chandra, Avinas; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Hirayama disease, a rare neurological disease, is characterized by insidious unilateral or bilateral muscular atrophy and weakness of the forearms and hands, without sensory or pyramidal signs. The objective of the study is to check the effect of physiotherapy intervention in this rare disease. Three cases with the weakness in grip and atrophy of forearm and hand was given the treatment using muscle stimulator, pressure biofeedback cuff, theraputty and strengthening exercise using weight and were performed 6 days a week for 8 weeks. Neck flexors strength was measured by using pressure biofeedback and upper limb strength was tested through Manual Muscle Testing grades. The deep neck flexors strength were improved using biofeedback cuff and muscle strength of forearm was improved by the resistive exercise using weight which was measured by MMT grading. Grip strength was also improved using theraputty and grip strengthening exercises. Physiotherapy Interventions can prevents the muscle wasting, joint stiffness and improves the muscle strength which significantly leads to improved quality of life.